Patient-centered Outcomes in Modern Endodontic Microsurgery: A Narrative Review - Haytham Jaha (Journal of Clinical and Diagnostic Research)
Endodontic Microsurgery (EMS), a minimally invasive approach to root canal treatment, has seen a notable increase in popularity due to its potential for enhanced outcomes. The present review seeks to evaluate the current state of Patient-Centered Outcomes (PCOs) in contemporary EMS, focusing on comparative analyses of surgical techniques, adjunctive therapies and the influence of technological advancements. The literature was examined to assess the effectiveness of various microsurgical techniques, including lasers, ultrasonic instrumentation and specialised irrigation solutions. Furthermore, the role of adjunctive therapies, such as regenerative techniques and antimicrobial agents, in improving treatment outcomes has been discussed. The impact of technological advancements, such as digital radiography and 3D imaging, on the precision and efficiency of microsurgical procedures is also explored. By providing a comprehensive overview of the existing evidence, the present review will assist clinicians in making informed decisions regarding the selection of microsurgical techniques and adjunctive therapies to optimise patient outcomes.